2016
DOI: 10.1002/2016ja022867
|View full text |Cite
|
Sign up to set email alerts
|

The quasi‐2 day wave activities during 2007 boreal summer period as revealed by Whole Atmosphere Community Climate Model

Abstract: The ensemble data assimilation version of the Whole Atmosphere Community Climate Model + Data Assimilation Research Testbed developed at National Center for Atmospheric Research is utilized to study the quasi‐2 day wave (QTDW) activities during boreal summer period of 2007. The westward wave number 3 (W3) and 4 (W4) modes intermittently dominated the QTDW oscillations at different times. The W3 peaked 4 times from day 172 to day 224 with the major peak at around days 199–206 being much stronger than the others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…The westward QTDW behaviors in WACCM + DART have been presented by Gu et al . [], which agree well with observations. Thus, the WACCM + DART can also provide reasonable analysis results for eastward QTDW.…”
Section: Waccmsupporting
confidence: 92%
See 2 more Smart Citations
“…The westward QTDW behaviors in WACCM + DART have been presented by Gu et al . [], which agree well with observations. Thus, the WACCM + DART can also provide reasonable analysis results for eastward QTDW.…”
Section: Waccmsupporting
confidence: 92%
“…Second, the E2 peaks in the lower mesosphere and upper stratosphere, while the westward QTDWs maximize in the mesopause region [ Yue et al ., ]. Third, the E2 is amplified by the mean flow instabilities of the winter westerly in the mesosphere, and the amplification of the westward QTDWs is related with the summer easterly jet [ Gu et al ., ]. Fourth, the E‐P flux vectors of E2 propagate downward in the mesosphere, which indicates a source for E2 in the upper mesosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Advanced Level Physics High Altitude version of the Navy Operational Global Atmospheric Prediction System (NOGAPS‐ALPHA) reanalysis data set shows that the interannual variations of the QTDW during the boreal summer period are dependent on the strength of the summer easterlies, and stronger summer easterlies provide larger forcing for its amplification (McCormack et al, ). Recently, Gu, Liu, Pedatella, Dou, & Shu () found that the strength of the summer easterlies is also responsible for selective amplification of the QTDWs with different zonal wave numbers. The W2 QTDW peaks with stronger summer easterlies than the W3 mode.…”
Section: Introductionmentioning
confidence: 99%
“…Weaker wave number 2 (W2) and 4 (W4) modes have also been identified (Gu, Liu, Li, Dou, Wu, et al, ; Gu, Liu, Pedatella, Dou, Li, et al, ; Tunbridge et al, ). In the Northern Hemisphere, the QTDW peaks intermittently from June to August with the W3 and W4 modes being equally strong (Gu, Liu, Pedatella, Dou, & Shu, ; McCormack et al, ; Pancheva et al, ). Generally, the QTDWs during the austral summer period are stronger than those during the boreal summer period.…”
Section: Introductionmentioning
confidence: 99%